Empowering Eleventh Graders’ Speaking Proficiency through a Humanistic Approach - Harefa, Afore Tahir; Zebua, Feliks Rejeki Sotani (Journal of English Language and Education, 2025)
This study investigates the implementation of a Humanistic Approach—emphasizing self-esteem, emotional engagement, and student-centered learning—to improve the speaking abilities of eleventh-grade students at a senior high school in expressing feelings of love during the 2024/2025 academic year. Utilizing Classroom Action Research (CAR), the intervention aimed to address challenges such as low self-confidence, limited vocabulary, and reliance on traditional teaching methods. The research was conducted in two cycles, each involving stages of planning, action, observation, and reflection. Data were gathered through observation sheets, oral tests, and video recordings. Findings indicate that the Humanistic Approach significantly enhanced students’ speaking fluency. While Cycle I showed only modest gains, Cycle II demonstrated substantial improvement, with 79.16% of students reaching the expected competency levels. These results underscore the effectiveness of a humanistic, student-centered methodology in creating a supportive environment that fosters oral language development.